Journal of technical education seience (Ho Chi Minh city University of Technology and Education, 2018)
Contents: Modeling the freezing process of turmeric starch to determine the rate of freezing; Adsprption of reactive dye by keransite beads in a batch abd fixed bed column mode; Copper nâoparticles immobilized on cation exchange resin as in effective disinfectan for removal of pathogenic bacteria in water treatment;...